2021
DOI: 10.3390/ijerph182212123
|View full text |Cite
|
Sign up to set email alerts
|

Do Organizational Health Climates and Leader Health Mindsets Enhance Employees’ Work Engagement and Job Crafting Amid the Pandemic?

Abstract: Although the COVID-19 pandemic has resulted in many health- and stress-related symptoms among employees, surprisingly few studies have assessed the effect of a health-promoting organizational climate or leadership on employee work outcomes. To fill this gap, our research proposed and tested a moderated mediation model involving perceived organizational health climate (POHC), leader health mindset (LHM), work engagement, and job crafting. Our propositions were tested using two-wave data collected from 301 South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 56 publications
(113 reference statements)
0
33
0
Order By: Relevance
“…Besides, evidence emerged from the study of 177 employed residents of Matabeleland South Region in Zimbabwe that providing for employees' health and safety needs during COVID-19 will boost employee engagement (Moyo, 2020). Shin and Hur (2021) confirmed that maintaining work attitudes and behavior in times of COVID-19 crisis depend on perceived organizational health climate (POHC) and leader's health mindset (LHM) based on a study of 301 South Korean employees. POHC indicates the perceptions of organizational policies and practices that support employees' physical and psychological health.…”
Section: Covid-19 Organizational Level Constructsmentioning
confidence: 87%
“…Besides, evidence emerged from the study of 177 employed residents of Matabeleland South Region in Zimbabwe that providing for employees' health and safety needs during COVID-19 will boost employee engagement (Moyo, 2020). Shin and Hur (2021) confirmed that maintaining work attitudes and behavior in times of COVID-19 crisis depend on perceived organizational health climate (POHC) and leader's health mindset (LHM) based on a study of 301 South Korean employees. POHC indicates the perceptions of organizational policies and practices that support employees' physical and psychological health.…”
Section: Covid-19 Organizational Level Constructsmentioning
confidence: 87%
“…self‐evaluated performance, altruism, and happiness through health behaviors. 13 , 16 , 17 , 18 , 19 As for the effectiveness of health culture in ensuring workers' health in times of crisis, it has been reported that a good health climate, which is closely related to health culture, was linked to job crafting behavior through work engagement under COVID‐19, 26 and that the presence of health climate in a medical institution with COVID‐19 practices led to a reduction in perceived stress of medical personnel. 27 However, there have been no reports on the relationship between health culture and the implementation of infection control measures in the workplace during a pandemic, as far as we know.…”
Section: Discussionmentioning
confidence: 99%
“…Before the outbreak of the COVID-19 pandemic, studies demonstrated the influence of work engagement on employees' workplace well-being and job satisfaction [43]. There are also antecedents like work values, job crafting, organizational support, and working conditions, that predict work engagement [10,48]. However, most of the studies have been neglecting teachers and focusing more on health workers.…”
Section: Work Engagement and Job Satisfactionmentioning
confidence: 99%
“…Teachers' readiness, competence level, and perceived or actual organizational support have hampered the processes of education transformation during COVID-19. Resulting from these setbacks, many teachers still prefer face-to-face or, at least, blended methods [3,10]. In respect to actual organizational support, a survey jointly done by UNESCO, the World Bank, and UNICEF found only half of the surveyed countries had offered additional training to teachers on distance education.…”
Section: Introductionmentioning
confidence: 99%